Analysis of the Impact of Merger and Acquisition on Customer Satisfaction and Loyalty of Banking Companies in Indonesia - Alexander, Gloria; Tetimau, Felicia Edlyn; Mahendra, Adrian; Linawati, Nanik (PT Mattawang Mediatama Solution, 2025)
This study observes the influence of mergers and acquisitions (M&A) towards customer satisfaction and loyalty of banking companies in Indonesia. It investigates how M&A activities affect consumer perceptions, service quality, and brand trust. Using survey data from news articles & customers of companies that have undergone M&A between 2018 and 2023, this study uses a quantitative approach with statistical analysis, including regression models and correlation analysis, to assess shifts in customer sentiment. The results acknowledge that while M&A can create operational efficiencies and expand service offerings, they sometimes lead to short-term decrease in customer satisfaction due to service disturbance and brand identity changes. Customers possibly encounter uncertainty about the product quality, pricing readjustments, and consistency of the service, affecting their general satisfaction. Nevertheless, companies with effective post-M&A combination, containing transparent communication, service consistency, and customer engagement, may maintain customer loyalty. Furthermore, brand reputation and trustworthiness play a big role in building post-M&A consumer behavior. Customers tend to remain loyal when they recognize stability and upgraded benefits after the merger. Though M&A develop opportunities for business growth, they also pose a threat to customer relationships if not executed correctly. Understanding these interactions is essential for companies to direct consumer doubts, enhance customer loyalty strategies, and maximize the long-term advantages of M&A.